V-Share: An Energy Efficient Collaborative Video Download and Sharing Application using Ad-hoc Cloud - Santhi, G (International Journal of Computer Sciences and Engineering, 2025)
Video download and sharing is one of the most popular applications in the field of mobile computing. Reducing the energy consumption of the mobile devices is a major challenge in sustaining multimedia applications. In this work, an adaptive framework called V-Share is developed for group of users with common interest to collaboratively download a video file from the cloud and share it among them. In V-Share, each node downloads only a segment of video file and the downloaded segments are reassembled and merged into a complete file by the coordinator node and then it is shared to all users of the ad-hoc group. Only the mobile nodes with relatively good battery level participate in download process whereas the nodes with low battery level remain futile. This greatly reduces the battery consumption of the mobile devices. Seamless connectivity is established between the mobile devices and the cloud using 3G and WiFi links enable cooperation among smart phones to smoothen the service.